Enhanced terahertz third-harmonic generation by bound states in the continuum in graphene grating-like metamaterial - Wang, Baoku; Liu, Jing; Cui, Jinhui; Liu, Jialin; Tian, Fengjun; Sun, Weimin; Li, Li (Frontiers in Physics, 2023)
Nonlinear metamaterials hold great promise for enhanced terahertz harmonic generation. Here, we numerically investigate enhanced terahertz third-harmonic (THG) by exploiting the symmetry-protected bound states in the continuum (BICs) in graphene grating-like metamaterial. By symmetry breaking of metamaterial, BICs transform into quasi-BICs. The high Q-factor and strong localized field enhancement is achieved at quasi-BICs, leading to boosting THG process with low incident intensity of fundamental frequency. The THG conversion efficiency reaches 3.1% at the incident intensity of 100 kW/cm2. The remarkably enhanced nonlinear optical process in the proposed nonlinear metamaterial constitutes an outstanding platform for on-chip terahertz nonlinear conversion applications.